Paediatrics and child health - edited by H.M. Coovadia; D.F. Wittenberg (Oxford University Press, 2004)
Particularly suitable for South African health care professionals, first-line practitioners, and medical students, this comprehensive introduction to pediatrics and child health illustrates primary health care applications, and uses South African examples to highlight local health problems